2008
DOI: 10.1371/journal.pone.0003105
|View full text |Cite
|
Sign up to set email alerts
|

Systems Biology of the Clock in Neurospora crassa

Abstract: A model-driven discovery process, Computing Life, is used to identify an ensemble of genetic networks that describe the biological clock. A clock mechanism involving the genes white-collar-1 and white-collar-2 (wc-1 and wc-2) that encode a transcriptional activator (as well as a blue-light receptor) and an oscillator frequency (frq) that encodes a cyclin that deactivates the activator is used to guide this discovery process through three cycles of microarray experiments. Central to this discovery process is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
186
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(201 citation statements)
references
References 89 publications
(242 reference statements)
13
186
1
1
Order By: Relevance
“…changes in transcriptional levels of many different families of genes drive physiological and developmental changes (Dong et al 2008;Greenwald et al 2010). These changes in transcription were observed over a period of time broader than in our microarray experiment.…”
Section: Discussionmentioning
confidence: 61%
“…changes in transcriptional levels of many different families of genes drive physiological and developmental changes (Dong et al 2008;Greenwald et al 2010). These changes in transcription were observed over a period of time broader than in our microarray experiment.…”
Section: Discussionmentioning
confidence: 61%
“…On one hand, light-dependent splicing has been shown in fungi (49,69), but if this mechanism were at work, additional bands resulting from (probably nonfunctional) truncated versions of CBH1 should have been detected on Western blots for light-grown cultures, which was not the case. However, clock regulation of ribosome biogenesis (but not transcriptional regulation of ribosome genes) has been shown and, hence, provides a means for posttranscriptional regulation of clock-controlled genes (11). Because of the crucial importance of light for resetting of the circadian clock, such a mechanism is likely to also be affected by light, which would provide a reasonable explanation for posttranscriptional regulation of cellulase gene expression by light.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, these signaling systems have functions in stress response, fungicide resistance, and development. Interestingly, it was shown that several components of the N. crassa two-component phosphorelay system are clock controlled (730). According to the classification system established in reference 731, T. atroviride, T. virens, and T. reesei have histidine kinases belonging to classes I, II, III, IV, V, VI, VIII, IX, X, and XI (see Fig.…”
Section: Protein Kinasesmentioning
confidence: 99%